State pension eligibility age and retirement behaviour: Evidence from the United Kingdom household longitudinal study - Adriaan Kalwij; Ricky Kanabar (University of Essex, Institute for Social and Economic Research (ISER), 2022)
We examine individuals' retirement behaviour in response to changes in the State Pension eligibility age introduced in various Pension Acts in the UK. The findings show the probability of retirement increases sharply once individuals become eligible for State Pension, by 40 pp and 34 pp for men and women respectively. We find no empirical support for men or women adjusting their expected retirement age upwards in response to an increase in the SP eligibility age. Our findings suggest that whilst changes in the State Pension eligibility age are important for individual's actual retirement, they do not induce individuals to revise their expected retirement age and this can result in suboptimal retirement planning. The latter can be problematic for those who rely disproportionately on State Pension as their main source of income and, arguably, targeted communication campaigns are needed to improve retirement planning.
Keywords: J26; 330; Retirement; Expectations; United Kingdom Household Longitudinal Study